1979
DOI: 10.2136/sssaj1979.03615995004300030016x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Burning on Chaparral Soils: II. Soil Microbes and Nitrogen Mineralization

Abstract: Undisturbed moist and dry soil slabs collected from beneath two species of chaparral plants were burned at varying intensities in the laboratory. Treatment by intense burning over dry soil destroyed 67% of the total N and produced large amounts of NH4+. Treatment by intense and moderate burning over moist soil slabs removed only 25% of the total N, and a large portion of the remaining organic N was quickly ammonified after the fire by reinvading heterotrophic bacteria and later by fungi. All three burning trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(35 citation statements)
references
References 0 publications
2
32
1
Order By: Relevance
“…(4). From such observational evidence, researchers have suggested that spore-forming bacteria thrive after fires because they either survive the heat generated by fires or rapidly colonize recently burned soils (21,55). In contrast to the diversity of nifH sequence types recovered at our study area, amplifiable amoA sequences formed only four separate clusters (AO1, AO2, AO3, and AO4), all of which were most closely related to Nitrosospira spp.…”
Section: Vol 71 2005 N-cycling Bacterial Communities After Forest Fmentioning
confidence: 53%
See 1 more Smart Citation
“…(4). From such observational evidence, researchers have suggested that spore-forming bacteria thrive after fires because they either survive the heat generated by fires or rapidly colonize recently burned soils (21,55). In contrast to the diversity of nifH sequence types recovered at our study area, amplifiable amoA sequences formed only four separate clusters (AO1, AO2, AO3, and AO4), all of which were most closely related to Nitrosospira spp.…”
Section: Vol 71 2005 N-cycling Bacterial Communities After Forest Fmentioning
confidence: 53%
“…The immediate effect of fire on the soil microbial biomass depends on the intensity and duration of the fire and can range from complete sterilization to little or no effect (4,55). Reductions in the total soil microbial biomass due to fire can persist for decades (21,22,42). However, rapid recolonization of specific microbial groups has also been observed, and fire has even been reported to stimulate microbial numbers and activity shortly after the burn, potentially through the release of readily utilizable C and N substrates (2,4,20,55).…”
mentioning
confidence: 99%
“…The substantial increases in N0 3 --N following burning are most likely produced by increased nitrification rates resulting from the high NH 4 + -N availability, perhaps coupled with the denaturation of alielopathic nitrification inhibitors, which are known to be present in ponderosa pine litter and soils (Lodhi and Killingblrck, 1980). However, decreased nitrification might, also be expected because of selective mortality of nitrifying bacteria, which appear to be particularly sensitive to soil heating (Dunn and DeBano, 1977;Dunn et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Fire intensity increases as the amount of biomass burned per unit area increases. In laboratory experiments, the amount of SOM remaining after a fire decreased with an increase in fire intensity (Dunn et al 1979). However, no coherent results related to the changes of SOM have been observed in field studies of slash-and-burn.…”
Section: Introductionmentioning
confidence: 90%